SURFACE PREPARATION OF PRODUCTS MADE FROM Д16T ALLOYS PRIOR TO APPLICATION OF VACUUM-PLASMA COATINGS - S. Ivaschenko; S. Koida (Наука и техника)
The paper presents results of  investigations on qualitative and quantitative characteristics of impurities on the surface of products made from aluminium alloy Д16Т .It has been shown that the main impurities of the products made from alloy Д16Т  are carbo-hydrates of paraffin and methanoic series.  In order to obtain high quality coating a technological process pertaining to surface cleaning prior to application vacuum-plasma coatings must include out- and intra-chamber treatments.